DWT Domain Information Hiding Approach Using Detail Sub-band Feature Adjustment - Qiudong Sun; Ping Guan; Yongping Qiu; Wenying Yan (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In recent years, many algorithms based on HVS and DWT had been proposed for watermarking. But most of them aimed at the binary iconic watermark. So they are unsuitable for embedding other format watermarks such as the text file, the gray image or even the color image. This paper proposed a multi-format data source file supporting algorithm for watermarking and information hiding. Firstly, the algorithm transformed a source file into a binary watermark sequence and put redundant encoding and random scrambling on it. Then, the algorithm selected two neighboring blocks each time from the Hilbert scanning sequence of the host image blocks, and transformed them by DWT. Lastly, according to the different codes of each two sequential watermark bits, the algorithm chose one of two thresholds of just noticeable difference (JND) to modify the average value features of two corresponding detail sub-bands to insert the watermark into the host image. Extracting hidden information only to need the embedded image without the original host images and the data source file, implemented the blind extraction to improve the security of secret information. The experimental results show that the embedded watermark is invisible, and the algorithm is robust to common image processing operations. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2934